Global and local fundamental frequency variation and larynx height: Some preliminary observations - Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1984)
The paper presents data on the relation between fundamental frequency declination and larynx height, and between the stress determined fundamental frequency variation and larynx height. The results can be summarized as follows: a) Fo declination seems to be accompanied by a concomitant declination of larynx height, b) the Fo rise from stressed to the first posttonic syllable in Standard Danish is accompanied by two different patterns of larynx height variation: in one the larynx rises, in the other it lowers. The findings are discussed in the light of theories for the production of Fo.